Analisis Pemahaman Konsep dalam Menyelesaikan Soal Geometri Dimensi Tiga Pada Peserta Didik SMK di Kota Makassar - Herwandi; Habiba Ulfahyana (Jurnal Penalaran dan Riset Matematika, 2023)
This type of research is descriptive research. This study aims to determine the understanding of concepts in solving three-dimensional geometry problems in class XI students of SMK Muhammadiyah 3 Makassar. The population in this study were all students of class XI SMK Muhammadiyah 3 Makassar. Furthermore, selecting samples with Cluster Random Sampling technique. The selected sample in this study is class XI Accounting Department. From this sample, interviews will be continued with 9 students consisting of 3 students in the high category, 3 students in the medium category, and 3 students in the low category. The instruments in this study in the form of concept understanding tests and interview guidelines used to determine the understanding of concepts in solving three-dimensional geometry problems in class XI students of SMK Muhammadiyah 3 Makassar. The data analysis technique in this study is descriptive statistical analysis with the aim of describing the understanding of mathematical concepts of students in class XI SMK Muhammadiyah 3 Makassar. Based on the results of data analysis and discussion that has been stated, the conclusion in this study is the understanding of concepts in solving geometry problems of three dimensions in class XI students of SMK Muhammadiyah 3 Makassar is on the indicators: (1) Concept understanding on indicator I, namely giving examples and not examples of a concept by 91%, (2) Concept understanding on indicator II, namely presenting concepts in various forms of mathematical representation by 53%, and (3) Concept understanding on indicator III, namely applying concepts or algorithms in problem solving by 57%.